Gender Wage Gap in Thailand - World Bank (Washington, DC, 2022)
The gender wage gap in Thailand is much less significant than in most countries in the world. The average hourly wage among female workers, in fact, slightly surpasses that of males. This highly equitable gender wage pattern is seen at all levels of the wage distribution. Female representation is also quite equal at all levels of wages; the likelihood of finding females in low-wage jobs is as high as in high-wage jobs. One important factor driving this gender wage parity is the higher educational attainment among female workers.